Optimalisasi Pojok Baca dalam Meningkatkan Literasi Anak Usia Dini (Taman Kanak-kanak) di Desa Kibang Kecamatan Metro Kibang - Yola Rosiani; Finadin Ahlul Nesly Budiani; ⁠Resti ⁠Fauziah; Luqy Khusaini Ahmad; Reka Aulia Ramadhani; Renanda Nurfatya; Wiwin Muslikhah; Refi Yoanda R.A; Mat Jalil (PADMA, 2025)
Abstract: This study aims to analyze the optimization of a Reading Corner as an effort to improve early childhood literacy in a kindergarten located in Kibang Village, Metro Kibang District. The research background encompasses limited educational infrastructure, the dominance of local language use that hinders instructional communication, and the low reading habits in children’s home and school environments. The study employs a descriptive qualitative approach with a case study method. Research subjects include teachers, children aged 4–6 years, parents, and village officials. Data were collected through participatory observation, semi‑structured interviews, and documentation, then analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The findings show that the Reading Corner increases children’s reading interest, expands their Indonesian vocabulary, promotes more participatory teacher–child interaction, and encourages greater parental involvement in literacy activities. This intervention effectively reduces language barriers and offers a practical solution to the lack of educational facilities. The Reading Corner serves not only as a physical reading facility but also as a catalyst for a community‑based literacy ecosystem that can be replicated in other rural areas facing similar challenges. Abstrak: Penelitian ini bertujuan menganalisis optimalisasi Pojok Baca sebagai upaya meningkatkan literasi anak usia dini di TK Desa Kibang, Kecamatan Metro Kibang. Latar belakang penelitian mencakup keterbatasan infrastruktur pendidikan, dominasi bahasa daerah yang menghambat komunikasi pembelajaran, serta rendahnya kebiasaan membaca di lingkungan anak. Penelitian menggunakan pendekatan kualitatif deskriptif dengan metode studi kasus. Subjek penelitian meliputi guru, anak usia 4–6 tahun, orang tua, dan perangkat desa. Data dikumpulkan melalui observasi partisipatif, wawancara semi-terstruktur, dan dokumentasi, kemudian dianalisis menggunakan model Miles dan Huberman. Hasil penelitian menunjukkan bahwa Pojok Baca meningkatkan minat baca anak, memperluas kosakata bahasa Indonesia, mendorong interaksi guru–anak yang lebih partisipatif, serta meningkatkan keterlibatan orang tua dalam kegiatan literasi. Intervensi ini terbukti mengurangi hambatan bahasa dan memberikan solusi praktis terhadap keterbatasan fasilitas pendidikan. Pojok Baca berfungsi tidak hanya sebagai sarana fisik membaca, tetapi juga sebagai penggerak ekosistem literasi berbasis komunitas yang dapat direplikasi di wilayah pedesaan dengan tantangan serupa.